Damage potential and control measures of Necrobia rufipes (De Geer) (Coleoptera: Cleridae) on dry fish with plant materials (Bangladesh Journal of Scientific and Industrial Research, 2013)
As a source of high protein content, fish is one of the major categories of foods consumed by human beings. In Bangladesh, fish provides the main and the cheapest source of animal protein in the diet of all walks of people. The process of drying and salting have been practised for fish preservation through centuries. Feeding by the larvae and adults of Necrobia rufipes (De Geer) causes quantitative loss of dried or cured fish and also leads to fragmentation and to quality losses and contamination by insects' bodies and cast skins. In our present study, about 20% damage was caused by N. rufipes in a storage period of six months (April to September). For preservation of dry fishes, five plant based materials namely Neem, Nishinda, Eucalyptus, Turmeric powder, Mehagoni and ash were evaluated. Each of the plant leaf powder at a concentration of 5 gm was uniformly mixed with 50 gm Punti dry fish and placed in a Petri dish (10 cm diam.). Five newly emerged (0-24 hrs old) larvae and adults of N. rufipes were introduced into each Petri dish. Neem leaf powder exerted the best result followed by turmeric powder, Nishinda, ash, Eucalyptus and Mehagoni leaf powders for preventing the larval infestations. Turmeric powder exerted the best result followed by Neem, Euclyptus, Mehagoni, Nishinda leaf powder and mehagoni oil- cake for ceasing infestation of dry fishes. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15409 Bangladesh J. Sci. Ind. Res. 48(1), 19-24, 2013